Malaria and Donor Deferral at King Abdulaziz University Hospital in Saudi Arabia: A Practice Review - Salwa I. Hindawi,; Fatin M. Al Sayes, (Journal of King Abdulaziz University: Medical Sciences, 2023)
One of the major occurrences initially documented of transmittedtransfusion of Malaria through blood transfusion remains uncommon, but medically serious and lethal. Several regions in Saudi Arabia documented Malaria as major health problem. Since 1958, blood establishments deferred donors based on history disclosure and previous illness to minimized risk. Careful inquiring is essential for identifying travel information and disease history to defer those at risk. Our aim is to estimate the prevalence of malaria parasites in random donors, review the efficiency practice in donor deferral, and compare our policy to other international policies. Retrospective study on record examination of blood donor questionnaire and testing files in Blood Transfusion Services at University Hospital from 2005- 2010. Results provided extensive baseline data; total donor in 2006 was 2378 compared to 1987, in 2010 less number of deferral was presented. In the past five years (2006-2010), deferral rate was 22.84% and 4.2% of total donors, thus still high. Since early 2000, existing policy of blood donor deferral was adapted. Updated essential policy in accepting donors is required; suitable deferral procedures, accurate methods with proper laboratory viewing may diminish the danger factor in the coming years and thus, eliminating malaria among blood donors.